Myosin binding protein-C activates thin filaments and inhibits thick filaments in heart muscle cells - Thomas Kampourakis; Ziqian Yan; Mathias Gautel; Yin‐Biao Sun; Malcolm Irving (2014)
Significance Myosin binding protein-C (MyBP-C) is a regulatory protein of heart muscle. Mutations in MyBP-C are frequently associated with heart disease, but the mechanism of action of MyBP-C is poorly understood. By characterizing the effects of its N-terminal domains on the structures of the thin and thick filaments in contracting heart muscle cells, we showed that MyBP-C stabilizes the ON state of thin filaments and the OFF state of thick filaments. The results lead to a model for the control of heart muscle contraction in which the regulatory functions of the thin and thick filaments are coordinated by MyBP-C, providing an integrated framework for the design and development of therapeutic interventions in heart disease.